Implementation with near complete information: The case of subgame perfection - KUNIMOTO, Takashi (Institutional Knowledge at Singapore Management University, 2009)
While monotonicity is a necessary and almost sufficient condition for Nash implementationand often a demanding one, almost any (non-monotonic, for instance) socialchoice rule can be implemented using undominated Nash or subgame perfect equilibrium.By requiring solution concepts to have closed graph in the limit of completeinformation, Chung and Ely (2003) show that only monotonic social choice rules canbe implemented in the closure of the undominated Nash equilibrium correspondence.In this paper, we show that only monotonic social choice rules can be implemented inthe closure of the subgame perfect equilibrium/sequential equilibrium correspondence.Our robustness result helps understand the limits of subgame pefect implementation,which is widely used in applications. We discuss the implications of our result for theliterature on incomplete contracts.